2001
DOI: 10.1097/00000478-200101000-00004
|View full text |Cite
|
Sign up to set email alerts
|

Immunohistochemical Panels For Differentiating Epithelial Malignant Mesothelioma From Lung Adenocarcinoma

Abstract: Immunohistochemistry provides an important indicator for differential diagnosis between pleural malignant mesothelioma and lung adenocarcinoma, which have complex therapeutic and medicolegal implications. To pinpoint a reliable, restricted panel of markers, the authors evaluated the efficacy of select commercial antibodies in a series of patients with confirmed clinicopathologic diagnosis of mesothelioma or lung adenocarcinoma with the aid of multiple logistic classification tables. Specimens of 46 mesotheliom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

3
115
3
3

Year Published

2001
2001
2015
2015

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 126 publications
(124 citation statements)
references
References 32 publications
3
115
3
3
Order By: Relevance
“…16,17 In 1996, Doglioni et al 16 reported strong calretinin expression in all 36 epithelioid mesotheliomas, but only focal staining was found in 28 (10%) of 294 adenocarcinomas of various origins and in 10 (18%) of 55 squamous carcinomas also of various origins. While many subsequent investigations have confirmed the usefulness of calretinin immunostaining in the differential diagnosis between mesotheliomas and lung adenocarcinomas, 8,[18][19][20][21][22][23][24][25][26][27][28][29] only a relatively few studies have been published on the expression of this marker in squamous carcinomas of the lung. 3,6,26,30 In the present investigation, all of the mesotheliomas exhibited diffuse strong positivity for calretinin, thus confirming the findings of previous studies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…16,17 In 1996, Doglioni et al 16 reported strong calretinin expression in all 36 epithelioid mesotheliomas, but only focal staining was found in 28 (10%) of 294 adenocarcinomas of various origins and in 10 (18%) of 55 squamous carcinomas also of various origins. While many subsequent investigations have confirmed the usefulness of calretinin immunostaining in the differential diagnosis between mesotheliomas and lung adenocarcinomas, 8,[18][19][20][21][22][23][24][25][26][27][28][29] only a relatively few studies have been published on the expression of this marker in squamous carcinomas of the lung. 3,6,26,30 In the present investigation, all of the mesotheliomas exhibited diffuse strong positivity for calretinin, thus confirming the findings of previous studies.…”
Section: Discussionmentioning
confidence: 99%
“…8 This is in contrast to mesotheliomas in which MOC-31 reactivity has been reported in o10% of the cases and the staining was limited to a few cells or to small focal areas of the tumor. 8,21,50,51 Only a few studies with a limited number of cases have investigated the reactivity of this antibody with squamous carcinomas of the lung. 8,52 In one of these studies, 8 MOC-31 positivity was reported in all six (100%) of the squamous carcinomas investigated.…”
Section: Discussionmentioning
confidence: 99%
“…Calretinin is expressed in both the cytoplasm and nucleus. According to the literature, its expression in malignant mesothelioma varies, [3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20] but most authors report frequent expression in epithelioid malignant mesothelioma, with only few studies reporting expression below 90%. Interestingly, calretinin expression has been described in a wide variety of cells, including steroid-producing cells of the testis and ovary, adipocytes, eccrine-glands, keratinizing thymic epithelial cells and numerous tumors, for example Merkel cell carcinoma, Leydig cell tumors of the testis, esthesioneuroblastoma, adenomas of the adrenal gland, small cell carcinoma of the lung and adenomatoid tumor.…”
mentioning
confidence: 99%
“…Most of these markers, such as BerEP4, CD15, the thyroid transcription factor (TTF-1) and carcinoembryonic antigen (CEA) stain adenocarcinomas whereas calretinin and CK5/6 are positive in both benign and malignant mesothelial cells. [3][4][5][6][7][8] An appropriate panel of antibodies is useful to differentiate between mesothelioma and adenocarcinoma. Among markers of adenocarcinomas whatever their origin (CEA, BerEP4, CD15), BerEP4 is the most sensitive (80%) but at the same time is the least specific.…”
mentioning
confidence: 99%
“…Moreover, the epitope recognized by this antibody is not yet characterized. 4,[8][9][10][11] Although it seems that LeuM1 (anti-CD15) may be specific, it is less sensitive than the other antibodies. 12,13 Results on CEA sensitivity and specificity are very controversial in the literature due to the use of various monoclonal or polyclonal antibodies.…”
mentioning
confidence: 99%